(untitled) (SCIENCE TIME JOURNAL, 2026)
This paper investigates the application of smart and mobile technologies to English for Specific Purposes (ESP), with particular emphasis on Business English instruction. Drawing on an integrative review of empirical and theoretical literature, the study identifies four principal challenges confronting Business English learners—occupational vocabulary acquisition, motivational decline, professional communication competence, and learner autonomy—and examines how Mobile-Assisted Language Learning (MALL), artificial intelligence (AI), Web 2.0 applications, and social networking tools may address these challenges. The paper reviews smart education strategies in high-performing economies (the Netherlands, Australia, South Korea) and evaluates the instructional affordances of six technology categories: wiki-based platforms, adaptive language applications, electronic dictionaries, social media channels, business-oriented video content, and slide presentation frameworks. Findings indicate that technology-enhanced ESP instruction, when anchored in authentic occupational contexts, substantially improves learner motivation, professional vocabulary range, written business communication, and presentation competence. The paper concludes with practical pedagogical recommendations and a call for context-specific empirical research with Uzbek Business English learners.